2018
DOI: 10.1158/0008-5472.can-17-0123
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Activators of Protein Phosphatase 2A for the Treatment of Castration-Resistant Prostate Cancer

Abstract: Primary prostate cancer is generally treatable by androgen deprivation therapy, however, later recurrences of castrate-resistant prostate cancer (CRPC) that are more difficult to treat nearly always occur due to aberrant reactivation of the androgen receptor (AR). In this study, we report that CRPC cells are particularly sensitive to the growth-inhibitory effects of reengineered tricyclic sulfonamides, a class of molecules that activate the protein phosphatase PP2A, which inhibits multiple oncogenic signaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 50 publications
5
69
1
Order By: Relevance
“…Considering the potential future development of DBK-1154 derivatives for GB therapy, DBK-1154 was evaluated in an acute rat pilot (non-GLP) toxicology study at doses up to 800 mg/kg daily. Consistently with previous SMAP in vivo studies (Sangodkar et al, 2017;McClinch et al, 2018), no significant body weight loss, deaths, or adverse behavioral or neurological effects were observed. The major morphologic finding was hepatocellular hypertrophy (panlobular) in all test article-treated groups, with increased severity as the dose level increased.…”
Section: Dbk-1154 With Higher Degree Of Brain/blood Distribution Ansupporting
confidence: 90%
See 3 more Smart Citations
“…Considering the potential future development of DBK-1154 derivatives for GB therapy, DBK-1154 was evaluated in an acute rat pilot (non-GLP) toxicology study at doses up to 800 mg/kg daily. Consistently with previous SMAP in vivo studies (Sangodkar et al, 2017;McClinch et al, 2018), no significant body weight loss, deaths, or adverse behavioral or neurological effects were observed. The major morphologic finding was hepatocellular hypertrophy (panlobular) in all test article-treated groups, with increased severity as the dose level increased.…”
Section: Dbk-1154 With Higher Degree Of Brain/blood Distribution Ansupporting
confidence: 90%
“…In addition to their different in vivo brain penetrance properties, NZ-8-061 seems to have cytostatic effects at the doses tested, whereas DBK-1154 most probably induces both, decreased proliferation and cell death. On the other hand, a SMAP derivative DBK-766 defective in PP2A reactivation (Sangodkar et al, 2017;McClinch et al, 2018), failed to suppress GB cell viability. The intracellular pathways involved in the apoptosis induction by DBK-1154 in vitro were not addressed in this concise communication, but clearly remains as an important future question to be addressed.…”
Section: Dbk-1154 With Higher Degree Of Brain/blood Distribution Anmentioning
confidence: 98%
See 2 more Smart Citations
“…In accordance with the major theme of this review, a recent study demonstrated that combination of SET targeting and tyrosine kinase inhibitor provides an effective therapeutic approach in human T‐cell acute lymphoblastic leukemia . Apart of small‐molecules targeting the PIPs, the novel series of orally bioavailable and nontoxic PP2A reactivator molecules with profound in vivo therapeutic activities in KRAS mutant lung cancers and castration‐resistant prostate cancer , provide a very encouraging example that PP2A indeed is druggable . In the context of this review, these small‐molecule PP2A activators were recently shown to transform the cytostatic MEK inhibitor responses to cytotoxic, and to greatly promote in vivo therapeutic effects of MEK inhibitor AZD6244 in two KRAS mutant lung cancer xenograft models .…”
Section: Therapeutic Targeting Of Pp2amentioning
confidence: 60%